Chronic administration of recombinant IL-6 upregulates lipogenic enzyme expression and aggravates high-fat-diet-induced steatosis in IL-6-deficient mice - Margarita Vida; Ana Luisa Gavito; Francisco Javier Pavón; Dolores Bautista; Antonia Serrano; Juan Suarez; Sergio Arrabal; Juan Decara; Miguel Romero-Cuevas; Fernando Rodríguez de Fonseca; Elena Baixeras (The Company of Biologists, 2015)
Interleukin-6 (IL-6) has emerged as an important mediator of fatty acid metabolism with paradoxical effects in the liver. Administration of IL-6 has been reported to confer protection against steatosis, but plasma and tissue IL-6 concentrations are elevated in chronic liver diseases, including fatty liver diseases associated with obesity and alcoholic ingestion. In this study, we further investigated the role of IL-6 on steatosis induced through a high-fat diet (HFD) in wild-type (WT) and IL-6-deficient (IL-6−/−) mice. Additionally, HFD-fed IL-6−/− mice were also chronically treated with recombinant IL-6 (rIL-6). Obesity in WT mice fed a HFD associated with elevated serum IL-6 levels, fatty liver, upregulation of carnitine palmitoyltransferase 1 (CPT1) and signal transducer and activator of transcription-3 (STAT3), increased AMP kinase phosphorylation (p-AMPK), and downregulation of the hepatic lipogenic enzymes fatty acid synthase (FAS) and stearoyl-CoA desaturase 1 (SCD1). The HFD-fed IL-6−/− mice showed severe steatosis, no changes in CPT1 levels or AMPK activity, no increase in STAT3 amounts, inactivated STAT3, and marked downregulation of the expression of acetyl-CoA carboxylase (ACCα/β), FAS and SCD1. The IL-6 chronic replacement in HFD-fed IL-6−/− mice restored hepatic STAT3 and AMPK activation but also increased the expression of the lipogenic enzymes ACCα/β, FAS and SCD1. Furthermore, rIL-6 administration was associated with aggravated steatosis and elevated fat content in the liver. We conclude that, in the context of HFD-induced obesity, the administration of rIL-6 might contribute to the aggravation of fatty liver disease through increasing lipogenesis.